Age-of-onset or Behavioral Sub-types? A Prospective Comparison of Two Approaches to Characterizing the Heterogeneity within Antisocial Behavior - Burt, S. Alexandra (2011)
There are two common approaches to sub-typing the well-documented heterogeneity within antisocial behavior: age-of-onset (i.e., childhood-onset versus adolescence-onset; see Moffitt, 1993) and behavioral (i.e., physical aggression versus non-aggressive rule-breaking). These approaches appear to be associated, such that aggression is more characteristic of childhood-onset antisocial behavior whereas rule-breaking is linked to both child- and adolescence-onset antisocial behavior. However, it remains unclear which approach, if either, better explains the heterogeneity within antisocial behavior. We examined this question in a prospective sample of male twins, assessed at the ages of 11, 14, 17, and 24 years. Although the age-of-onset subtypes predicted adult antisocial behavior in the expected direction when analyzed alone, this association dissipated once we controlled for aggression and rule-breaking. Such findings suggest that the behavioral sub-types of antisocial behavior may be a stronger predictor of later antisocial outcomes than is their age-of-onset.